2019
DOI: 10.1080/01608061.2019.1666774
|View full text |Cite
|
Sign up to set email alerts
|

The Marketing Firm as a Metacontingency:Revealing the Mutual Relationships between Marketing and Finance

Abstract: This paper reveals the mutual relationship between a firm's marketing behavior and its financial consequences. With panel data from publicly traded companies covering 17 years, we obtained the total expenditures in marketing of each company to represent marketing behavior and five financial outcomes, depicting the reinforcers. Each metric was composed of frequency, magnitude, and delay dimensions. The results show mutual effects between investments in marketing activities (aggregate product of interlocking beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…However, in contrast with Park et al, that study shows that such a practice should be avoided, as advertising effectiveness is lower when sentiment is high. Finally, a recent meta-analysis in the organizational behavior literature (Porto & Foxall, 2019) documents that, across a large sample of nearly 12,000 public firms in the US and UK, financial gains only partially feed back to subsequent marketing investments. Thus, "marketing is effective in generating financial gains, but it is not a sustainable activity, requiring managers to inject more money to do more marketing" (Porto & Foxall, 2019, pp.…”
Section: Feedback Effectsmentioning
confidence: 99%
“…However, in contrast with Park et al, that study shows that such a practice should be avoided, as advertising effectiveness is lower when sentiment is high. Finally, a recent meta-analysis in the organizational behavior literature (Porto & Foxall, 2019) documents that, across a large sample of nearly 12,000 public firms in the US and UK, financial gains only partially feed back to subsequent marketing investments. Thus, "marketing is effective in generating financial gains, but it is not a sustainable activity, requiring managers to inject more money to do more marketing" (Porto & Foxall, 2019, pp.…”
Section: Feedback Effectsmentioning
confidence: 99%
“…Ganesan (2012) emphasized that numerous organizations have suggested that the value to business functions and financial performance established by the marketing function has become a critical concern. Moreover, Porto and Robert Foxall (2019) claimed that marketing expenditure is a decision of how much financial resource is allocated in operations that attract consumers to the organization’s products versus other non-marketing functions such as salary and administrative expenses. Hence, this paper proposes the marketing–finance relationship within SCF adoption a new vulnerability mitigation strategy at organizational level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the use of Equations 1 to 5 there is a range of applications for revealing effects on organizational practices, especially marketing practices that generate reinforcing or punishing effects for the firm. Porto and Foxall (2019) used Equation 5to reveal the changes in percentage points of the dimensions and of the types of reinforcers over the changes in percentage points of the marketing investments in a subsequent time (a choice of managerial effort geared toward the consumerate). Results have revealed that the reinforcer delay dimension was the most important influencer and, in general, an undermatching relation (inelasticity) is found -a high level of reinforcers is needed to generate small increments in subsequent marketing investments in relation to other company administrative investments.…”
Section: The Performance Of a Marketing Firmmentioning
confidence: 99%
“…Applications of the Marketing Firm Theory have been used to reveal firms' utilitarian financial gains or losses (Porto & Foxall, 2019;Porto & Foxall, 2020).…”
Section: The Performance Of a Marketing Firmmentioning
confidence: 99%